Collaborative public management: coordinated value propositions among public service organizations. Issue 6 (2nd June 2020) - Eriksson, Erik; Andersson, Thomas; Hellström, Andreas; Gadolin, Christian; Lifvergren, Svante
ABSTRACT: Drawing from collaborative public management, this article seeks to contribute to public service logic by focusing on what precedes the public service user's realization of value: the value proposition. A new care model for elderly people with multiple chronic diseases shows that coordinators with an inter-organizational mission, vertical and horizontal supporting structures, trust established through relationships, and recognition of service systems' embeddedness in social systems are pivotal for the ability of public service organizations to develop coordinated value propositions. The contribution to policy and practice is an increased understanding of a coherent, rather than fragmented, welfare system for users/citizens.